Prevalence and Associated Factors of Visual Hallucinations in Patients with Vascular Cognitive Impairment. (11th January 2021) - Chen, Chih-Lin; Hsu, Min-Hsien; Hung, Chao-Hsien; Chiu, Pai-Yi; Liu, Chung-Hsiang
Abstract : Visual hallucinations (VHs) are striking features for dementia, especially dementia with Lewy bodies (DLB). We aimed to study the frequency and associated factors of VH in vascular cognitive impairment (VCI) and investigate the feasibility of clinically diagnosing the mixed pathology of VCI with DLB. This is a multicentre registration study. A consecutive series of VCI patients with and without dementia were enrolled. Frequency of VH and associated factors, including age, gender, education, disease severity, DLB clinical features, vascular risk factors, cognitive function, and neuropsychiatric symptoms, were compared between VCI with VH (VH+) and without VH (VH−). Among the 1281 patients analysed, 155 (12.1%) had VH. The VH+ group was older (t = 5.07 ; p < 0.001 ), was more likely to be female (χ 2 = 13.46 ; p < 0.001 ), and has a higher clinical dementia rating (χ 2 = 70.51 ; p < 0.001 ). After adjusting for age, gender, and disease severity, the VH+ group had poorer cognition and more severe neuropsychiatric symptoms. The VH+ group was more associated with DLB features in fluctuating cognition (OR = 2.48 ; p < 0.001 ), parkinsonism (OR = 1.85 ; p = 0.001 ), rapid eye movement (REM) behavioral disorder (OR = 4.56 ; p < 0.001 ), and ≧2 DLB core features (OR = 26.01 ; p < 0.001 ). VCI patients with VH tend to have more severe dementia, neuropsychiatric symptoms, and poorer cognitive function. Additionally, highly associated with clinical DLB features in VCI with VH raised the possibility of mixed pathology with DLB in this group. More than two core features in VCI might help in diagnosing a mixed pathology with DLB.